Social distribution of diabetes, hypertension and related risk factors in Barbados: a cross-sectional study. Issue 12 (18th December 2015) - Howitt, Christina; Hambleton, Ian R; Rose, Angela M C; Hennis, Anselm; Samuels, T Alafia; George, Kenneth S; Unwin, Nigel
Abstract : Objective: To describe the distribution of diabetes, hypertension and related behavioural and biological risk factors in adults in Barbados by gender, education and occupation. Design: Multistage probability sampling was used to select a representative sample of the adult population (≥25 years). Participants were interviewed using standard questionnaires, underwent anthropometric and blood pressure measurements, and provided fasting blood for glucose and cholesterol measurements. Standard WHO definitions were used. Data were weighted for sampling and non-response, and were age and sex standardised to the 2010 Barbados population. Weighted prevalence estimates were calculated, and prevalence ratios were calculated for behavioural and biological risk factors by demographic and socioeconomic group. Results: Study response rate was 55.0%, with 764 women, 470 men. Prevalence of obesity was 33.8% (95% CI 30.7% to 37.1%); hypertension 40.6% (95% CI 36.5% to 44.9%); and diabetes 18.7% (95% CI 16.2% to 21.4%). Compared with women, men were less likely to be obese (prevalence ratio 0.5; 95% CI 0.4 to 0.7), or physically inactive (0.5; 0.4 to 0.6), but more likely to smoke tobacco (4.1; 2.5 to 6.7) and consume large amounts of alcohol in a single episode (4.6; 2.7 to 7.6). Both diabetes (0.83; 0.65 to 1.05) and hypertension (0.89; 0.79 to 1.02) were lower in men, but not significantly so. In women, higher educational level was related to higher fruit and vegetable intake, more physical activity, less diabetes and less hypercholesterolaemia (p 0.01–0.04). In men, higher education was related only to less smoking (p 0.04). Differences by occupation were limited to smoking in men and hypercholesterolaemia in women. Conclusions: In this developing country population, sex appears to be a much stronger determinant of behavioural risk factors, as well as obesity and its related risks, than education or occupation. These findings have implications for meeting the commitments made in the 2011 Rio Political Declaration, to eliminate health inequities.